Synthesis, In vitro and In silico Evaluation of a Series of Pyrazolines as New Anticholinesterase Agents - Altıntop, Mehlika D. (Letters in Drug Design & Discovery, 2020)
Background: Pyrazolines, electron-rich nitrogen carriers, are of great importance due to their potential applications for the treatment of many diseases including inflammation, infectious diseases and neurodegenerative disorders. Objectives: The purpose of this work was to synthesize new pyrazoline derivatives and evaluate their anticholinesterase effects. Methods: 1-Aryl-5-[4-(piperidin-1-yl)phenyl]-3-(3,4-dimethoxyphenyl)-4,5-dihydro-1H-pyrazoles (1-7) were synthesized via the treatment of 1-(3,4-dimethoxyphenyl)-3-[4-(piperidin-1-yl)phenyl]prop-2- en-1-one with arylhydrazine hydrochloride derivatives in acetic acid, whereas 1-aryl-5-[4- (morpholin-4-yl)phenyl]-3-(3,4-dimethoxyphenyl)-4,5-dihydro-1H-pyrazoles (8-14) were obtained by the treatment of 1-(3,4-dimethoxyphenyl)-3-[4-(morpholin-4-yl)phenyl]prop-2-en-1-one with arylhydrazine hydrochloride derivatives in acetic acid. Their inhibitory effects on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) were determined using a modification of Ellman’s spectrophotometric method. In silico docking and Absorption, Distribution, Metabolism and Excretion (ADME) studies were performed using Schrödinger’s Maestro molecular modeling package. Results: In general, piperidine derivatives were found to be more effective than morpholine derivatives on cholinesterases (ChEs). 1-Phenyl-5-[4-(piperidin-1-yl)phenyl]-3-(3,4-dimethoxyphenyl)- 4,5-dihydro-1H-pyrazole (1) and 1-(4-cyanophenyl)-5-[4-(piperidin-1-yl)phenyl]-3-(3,4- dimethoxyphenyl)-4,5-dihydro-1H-pyrazole (7) were identified as the most effective AChE inhibitors in this series with 40.92% and 38.98%, respectively. Compounds 1 and 7 were docked into the active site of human AChE (PDB code: 4EY7). Both the compounds were found to be capable of forming π-π stacking interactions with Trp286. Based on in silico ADME studies, these compounds are expected to have reasonable oral bioavailability. Conclusion: In the view of this work, the structural modification of the identified agents is going on for the generation of new anticholinesterase agents with enhanced efficacy.
Keywords: Acetylcholinesterase